Pengaruh Kualitas Sumber Daya Manusia, Sarana Dan Prasarana Terhadap Kinerja Pegawai Dengan Disiplin Kerja Sebagai Variabel Moderasi (Studi Pada Aparatur Sipil Negara Pemerintah Daerah Kabupaten Maybrat Provinsi Papua Barat Daya) - Radbaud Fanataf; Rahayu Puji Suci; Ana Sopanah; Adya Hermawati; Nasharuddin Mas (Bajang Institute, 2026)
Abstrak: The objective of this study is to analyze the effect of Human Resources Quality and Infrastructure on Employee Performance in the Regional Government of Maybrat Regency, with Work Discipline as a Moderating Variable. (A Study on Civil Servants of the Maybrat Regency Government). The research method used is quantitative. The population comprises all Civil Servants in Maybrat Regency, Southwest Papua Province, totaling 3,754 employees. The sample size was determined using the Slovin formula, resulting in a calculated figure of 120, which was rounded down to 60 employees. Based on the data, samples were selected using proportionate stratified random sampling. The researcher utilized Partial Least Square (P LS) for data analysis with SmartPLS version 4 software. The results indicate that better performance appraisal can drive improved employee performance. Surprisingly, a stronger Work Discipline is unable to drive employee performance improvements. Similarly, stronger Human Resources Quality fails to boost employee performance. Conversely, better Human Resources Quality is able to drive improved employee performance. Work Discipline cannot moderate the relationship between performance appraisal and employee performance. Infrastructure cannot moderate the relationship between Human Resources Quality and employee performance. Furthermore, Work Discipline is unable to moderate the relationship between Human Resources Quality and employee performance.